Comparative analysis of the vlasiator simulations and MMS observations of multiple Xline reconnection and flux transfer events - AkhavanTafti,M; Palmroth,M; Slavin,JA; Battarbee,M; Ganse,U; Grandin,M; Le,G; Gershman,DJ; Eastwood,JP; Stawarz,JE (Journal of Geophysical Research: Space Physics, 2020)
The Vlasiator hybridVlasov code was developed to investigate global magnetospheric dynamics at ionkinetic scales. Here, we focus on the role of magnetic reconnection in the formation and evolution of the magnetic islands at the lowlatitude magnetopause, under southward interplanetary magnetic field (IMF) conditions. The simulation results indicate that: 1) the magnetic reconnection ion kinetics, including the Earthwardpointing Larmor electric field on the magnetosphericside of an Xpoint and anisotropic ion distributions, are wellcaptured by Vlasiator, thus enabling the study of reconnectiondriven magnetic island evolution processes, 2) magnetic islands evolve due to continuous reconnection at adjacent Xpoints, ‘coalescence’ which refers to the merging of neighboring islands to create a larger island, ‘erosion’ during which an island loses magnetic flux due to reconnection, and ‘division’ which involves the splitting of an island into smaller islands, and 3) continuous reconnection at adjacent Xpoints is the dominant source of magnetic flux and plasma to the outer layers of magnetic islands resulting in crosssectional growth rates up to +0.3 RE2/min. The simulation results are compared to the Magnetospheric Multiscale (MMS) measurements of a chain of ionscale flux transfer events (FTEs) sandwiched between two dominant Xlines. The MMS measurements similarly reveal: 1) anisotropic ion populations, and 2) normalized reconnection rate ~0.18, in agreement with theory and the Vlasiator predictions. Based on the simulation results and the MMS measurements, it is estimated that the observed ionscale FTEs may grow Earthsized within ~10 minutes, which is comparable to the average transport time for FTEs formed in the subsolar region to the highlatitude magnetopause. Future simulations shall revisit reconnectiondriven island evolution processes with improved spatial resolutions.